A SURVEY OF INFESTATION OF COCONUT ERIOPHYID MITE, ACERIA GUERRERONIS KEIFER IN KONKAN REGION OF MAHARASHTRA (INDIA) - A. S. BAGDE; V. V. PASHTE (The Bioscan, 2014)
The coconut eriophyid mite was reported to cause damage in coconut plantations in Konkan region of Maharashtra (India). The survey was conducted in the month of April-May of every year i.e. 2004-05, 2005-06, 2006-07 and 2007-08 in selected villages of four districts of Konkan region. The infestation of eriophyid mites on the basis of per cent palm infestation as well as on the basis of nut infestation was more in Thane district (ranges between 73.23 to 84.40%) followed by Sindhudurg district (33.03 to 86.80%). The nut infestation in Thane district was mostly belongs to Grade III and ranges between 64.16 to 89.42%. The nut infestation in Thane district whereas in Sindhudurg, Ratnagiri and Raigad districts was most of the infested nuts belong to Grade II. However, during survey (2007-08) the highest nut infestation in Grade III was observed in Revedanda, Malgund and Dodamarg villages of Raigad, Ratanagiri and Sindhudurg districts, respectively with 43.45, 30.43 and 69.11 per cent infestation. Survey results can be concluded that the infestation of eriophyid mites to coconut in Thane district had reached to its maximum limit and was found to have started much earlier than in rest of the districts.